Employee Engagement and Employee Motivation Among Manufacturing Firms in Nigeria - Chinenye Maureen Nuel-Okoli; Ifeanyi Nuel Okoli (Trescode Green Organization, 2025)
This study examined the relationship between employee engagement and employee motivation in selected manufacturing firms in Anambra State. The study was based on Resource-Based Theory (RBT) and employed a cross-sectional research design. The target population comprised 320 employees from various departments within the organizations. A sample size of 123 workers was determined using Taro Yamane’s (1967) formula. Data were collected through structured questionnaires administered to randomly selected employees from manufacturing firms in Anambra State. The reliability of the measurement instrument was assessed using Cronbach's Alpha. Descriptive statistics were used to present the data, while Pearson’s correlation coefficient was applied to test the hypotheses. The study revealed that employee engagement positively and significantly relates to employee motivation in selected manufacturing firms in Anambra State. In conclusion, a positive work environment driven by motivated employees can also contribute to lower turnover rates, which is particularly beneficial in an industry where retaining skilled workers is vital for sustained success. To leverage the link between engagement and motivation, the study recommends that firms should focus on creating an engaging workplace culture. This could involve regular feedback sessions, team-building activities, and ensuring that employees feel valued and involved in decision-making processes.